2020
DOI: 10.12788/jhm.3445
|View full text |Cite
|
Sign up to set email alerts
|

A STEEEP Hill to Climb: A Scoping Review of Assessments of Individual Hospitalist Performance

Abstract: BACKGROUND: Although ensuring high-quality care requires assessment of individual hospitalist performance, current assessment approaches lack consistency and coherence. The Institute of Medicine’s STEEEP framework for quality healthcare conceptualizes quality through domains of “Safe,” “Timely,” “Effective,” “Efficient,” “Equitable,” and “Patient Centered.” This framework may be applicable to assessing individual hospitalists. OBJECTIVE: This scoping review sought to identify studies that describe variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
(277 reference statements)
0
8
0
Order By: Relevance
“…42 These two investigations Open access shed light on the impact of booster training on procedural skills in nonsurgeons but are imperfect as proxies for hospitalists, who are no longer trainees and have accumulated more experience. Insights from studies on monitoring hospitalist performance in non-procedural skills are also germane in concept, as they focus on collecting and reporting objective individual-level 16 and group-level metrics, 13 approaches applicable to procedural competence tracking. Ultimately, our study examines a population that has been overlooked in terms of ensuring competence, while highlighting the practical realities that must be overcome for the scalability of this work for other hospital medicine groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 These two investigations Open access shed light on the impact of booster training on procedural skills in nonsurgeons but are imperfect as proxies for hospitalists, who are no longer trainees and have accumulated more experience. Insights from studies on monitoring hospitalist performance in non-procedural skills are also germane in concept, as they focus on collecting and reporting objective individual-level 16 and group-level metrics, 13 approaches applicable to procedural competence tracking. Ultimately, our study examines a population that has been overlooked in terms of ensuring competence, while highlighting the practical realities that must be overcome for the scalability of this work for other hospital medicine groups.…”
Section: Discussionmentioning
confidence: 99%
“…7 8 Additionally, studies showing two decades of declining volume among internists (which included hospitalists and primary care physicians) 9 10 contribute to concerns about their procedural competency. 11 12 In contrast to a growing literature on metrics used to assess hospitalist performance in non-procedural realms, [13][14][15][16] there has been no previous objective skills assessment of hospitalists who are already permitted to perform procedures, an…”
Section: Introductionmentioning
confidence: 99%
“…Academic hospitalists are tasked with dual educational and operational missions: to effectively teach learners and efficiently care for patients. [1][2][3] Most hospitalists lack formal training in these domains and struggle to balance these competing demands. 4 Peer observationin which one faculty member directly observes and provides structured feedback to another-improves educational outcomes, including learning climate, learner understanding, and retention.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] To our knowledge, peer observation programs have not extended to clinical operations or the role of the hospitalist to optimize clinical efficiency, workflow, and hospital throughput, although the track record in educational training suggests promise. 1,13 Given the significance of this domain to hospitalist success, we created a peer observation program equally focused on educational and operational domains.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the Journal of Hospital Medicine, Dow and colleagues have advanced our understanding of the current state of individual-rather than group-level hospitalist performance measurement. 2 This scoping review identified 43 studies published over the last 25 years reporting individual adult or pediatric hospitalist performance across one or more of the STEEEP framework domains of performance: Safe, Timely, Effective, Efficient, Equitable, Patient Centered. 3 The most common domain assessed in the studies was Patient Centered (20 studies), and in descending order from there were Safe (16), Efficient (13), Timely (10), Effective (9).…”
mentioning
confidence: 99%